2021
DOI: 10.1101/2021.06.30.21259818
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Social isolation, loneliness and all-cause dementia: a longitudinal and imaging-genetic study in the UK Biobank cohort

Abstract: INTRODUCTION: Current findings of the relative influence of social isolation and loneliness on dementia are contradictory, and the potential neurobiological mechanisms are unclear. METHODS: We utilized the UK Biobank to investigate the relationships of social isolation and loneliness with dementia (n = 462,619). Neuroanatomical correlates were identified in a subset of participants (n = 32,263). The transcriptomic signatures of related brain changes were characterized by gene enrichment analysis. RESULTS: Aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 57 publications
0
2
1
Order By: Relevance
“…The findings are inconsistent with some prior studies that indicated that social isolation was associated with a higher likelihood of cognitive decline or functional disability 10,16 . One cohort study revealed that socially isolated people had reduced gray matter volumes in temporal, frontal, occipital, and subcortical regions, which were involved in memory and learning, and those changes were not confounded by loneliness 45 . Other studies, however, have suggested that the significant association between social isolation and dementia risk may be due to social isolation as an early consequence rather than a cause of dementia 46 .…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…The findings are inconsistent with some prior studies that indicated that social isolation was associated with a higher likelihood of cognitive decline or functional disability 10,16 . One cohort study revealed that socially isolated people had reduced gray matter volumes in temporal, frontal, occipital, and subcortical regions, which were involved in memory and learning, and those changes were not confounded by loneliness 45 . Other studies, however, have suggested that the significant association between social isolation and dementia risk may be due to social isolation as an early consequence rather than a cause of dementia 46 .…”
Section: Discussioncontrasting
confidence: 64%
“…10,16 One cohort study revealed that socially isolated people had reduced gray matter volumes in temporal, frontal, occipital, and subcortical regions, which were involved in memory and learning, and those changes were not confounded by loneliness. 45 Other studies, however, have suggested that the significant association between social isolation and dementia risk may be due to social isolation as an early consequence rather than a cause of dementia. 46 Therefore, more research is needed to identify plausible mechanisms by which social isolation might or might not lower the risk of MCR.…”
Section: Associations Between Social Isolation Loneliness and Mcrmentioning
confidence: 99%
See 1 more Smart Citation